1996
DOI: 10.1007/bf00019006
|View full text |Cite
|
Sign up to set email alerts
|

Phenylalanine ammonia-lyase gene structure, expression, and evolution in Nicotiana

Abstract: Phenylalanine ammonia-lyase (PAL) catalyzes the first reaction in the general phenylpropanoid pathway leading to the production of phenolic compounds with a significant range of biological function. A PAL gene we designated gPAL1, cloned from tobacco, consists of two exons separated by an intron of 1932 bp. Exon I, 398 bp, and exon II, 1747 bp, together encode a polypeptide of 715 amino acids. A putative TATA box and polyadenylation signal are found 144 bp upstream of the initiation codon and 193 bp downstream… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
58
0

Year Published

1997
1997
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(61 citation statements)
references
References 34 publications
(28 reference statements)
3
58
0
Order By: Relevance
“…Such putative channel complexes might be associated with specific isoforms of PAL, which is encoded by a multigene family in tobacco (Fukasawa-Akada et al, 1996) and most other species studied. Such complexes might direct Phe or cinnamate specifically into the production of G or S units, and partitioning of flux into these complexes might not be equally affected by down-regulation of PAL compared with C4H, particularly if different tobacco PAL forms are differentially sensitive to co-suppression by the bean PAL transgene.…”
Section: Genetic Manipulation Of Lignin Composition In Transgenic Tobmentioning
confidence: 99%
“…Such putative channel complexes might be associated with specific isoforms of PAL, which is encoded by a multigene family in tobacco (Fukasawa-Akada et al, 1996) and most other species studied. Such complexes might direct Phe or cinnamate specifically into the production of G or S units, and partitioning of flux into these complexes might not be equally affected by down-regulation of PAL compared with C4H, particularly if different tobacco PAL forms are differentially sensitive to co-suppression by the bean PAL transgene.…”
Section: Genetic Manipulation Of Lignin Composition In Transgenic Tobmentioning
confidence: 99%
“…The two Coupling of PAL and C4H in Tobacco 1545 families are represented by single-copy PAL genes in the two progenitor species, Nicotiana sylvestris and N. tomentosiformis (Fukasawa-Akada et al, 1996). In this study, PAL1 refers to the product encoded by the PAL gene of family I, described by Fukasawa-Akada et al (1996), and PAL2 refers to the product of the PAL gene from family II, as reported by Nagai et al (1994). To determine whether specific forms of PAL are associated with tobacco microsomes, we raised antibodies against synthetic peptide sequences specific for tobacco PAL1, tobacco PAL2, and bean PAL2 (Howles et al, 1996).…”
Section: The Nature Of Pal Associated With Microsomal Membranesmentioning
confidence: 99%
“…For raising antibodies specific to tobacco PAL proteins, the following amino acid sequences, derived from the available tobacco PAL sequences (Nagai et al, 1994;Pellegrini et al, 1994;Fukasawa-Akada et al, 1996), were used: VRDKSANG (positions 69 to 76 from tobacco PAL1) and VAQNGHQEMDFCVKV (positions 4 to 18 from tobacco PAL2). These sequences represent the few stretches that are unique between the different tobacco PAL forms.…”
Section: Generation Of Antibodies Specific For Tobacco and Bean Pal Fmentioning
confidence: 99%
See 1 more Smart Citation
“…They are derived from trans-cinnamic acid formed by deamination of L-Phe by L-Phe ammonia-lyase (PAL; EC 4.3.1.5). PAL is a tetrameric enzyme whose subunits are encoded by multigene families in most species studied (Cramer et al, 1989;Nagai et al, 1994;Wanner et al, 1995;Fukasawa-Akada et al, 1996). In tobacco (Nicotiana tabacum), PAL genes have a simple organization consisting of two families, each with two very closely related genes (Nagai et al, 1994;Pellegrini et al, 1994).…”
Section: Introductionmentioning
confidence: 99%